Field localization and rescattering in tip‐enhanced photoemission. Issue 1 (10th December 2012) - Yalunin, Sergey V.; Herink, Georg; Solli, Daniel R.; Krüger, Michael; Hommelhoff, Peter; Diehn, Manuel; Munk, Axel; Ropers, Claus; Hommelhoff, Peter; Kling, Matthias; Stockman, Mark
<x xml:space="preserve">Abstract</x> This article presents a quantum mechanical treatment of strong‐field photoelectron emission from nanostructures. The effects of a spatial inhomogeneity of the optical near‐field are identified. Furthermore, the importance of electron scattering at the surface is elucidated by contrasting simulations with and without backscattering. Convincing agreement with experimental data under various conditions is demonstrated.